Athletic trainer perceptions of life-work balance and parenting concerns - Eberman, L. E.; Kahanov, L. (Journal of Athletic Training, 2013)
Context: Life-work balance may be one reason for retention concerns among athletic trainers (ATs), yet evidence does not exist to support the supposition. Objective: To assess the perceptions of ATs regarding life-work balance, specifically on parenting issues. Design: Survey. Setting: Online survey at www.surveymonkey.com. Patients or Other Participants: A random sample of National Athletic Trainers' Association members (N = 9516) received the survey; 20.6% (n = 1962; male = 954, female = 816; age = 37 ± 10 years, experience = 13 ± 9 years) completed any portion of the survey. Most respondents worked in the college/university (34.5%, n = 657 of 1908) and secondary school settings (25.9%, n = 476 of 1908). A majority of participants (50.7%, n = 898 of 1770) were parents. Intervention(s): We calculated frequencies and percentages and used Mann-Whitney U tests and Kruskal-Wallis tests to identify the differences between sexes and among job settings on life-work balance measures among parents. Main Outcome Measures: The questionnaire included 8 life-work balance items, 7 parenting challenge items, and 3 nonparent items. Results: The results indicate that sex and setting significantly affected perceptions about parenting. Males articulated a stronger sense of difficulty in finding balance as a working parent (P < .001; 1.95 ± 1.98). Females felt more strongly than males that managing work and family was stressful (P = .04; 3.86 ± 1.13) and caused burnout (P = .004; 3.50 ± 1.24), and that their energy tended to fall short of their needs (P < .001; 3.74 ± 1.15). The decision not to have children was strongly affected by the work setting (P = .014; 3.37 ± 1.42). Both college/university (4.14 ± 0.85) and secondary school (4.03 ± 0.90) ATs would prefer to spend more time at home, as compared with ATs in other settings (P < .001). College/university ATs (P = .025; 3.17 ± 1.23) felt most strongly that their families were neglected because of work. In none of the settings did ATs feel that their employment settings were particularly tolerant of their parenting responsibilities (P = .027; 1.72 ± 1.97). Conclusions: Male and female employees had similar perceptions of life-work balance, but occupational setting may affect these perceptions.